Non-linear association between serum vitamin D and bacterial vaginosis in U.S. women: analysis from NHANES 2001–2004 - Liu, Ming; Xiang, Jingyu; Zhang, Miao; Zhang, Yifang; Liu, Jian (Frontiers in Nutrition, 2025)
BackgroundPrevious studies have reported inconsistent associations between serum vitamin D levels and bacterial vaginosis (BV). Therefore, this study aimed to comprehensively investigate the relationship between serum vitamin D concentrations and BV risk among adult women in the United States.MethodsData from the National Health and Nutrition Examination Survey (NHANES) 2001–2004 were analyzed. Multivariate logistic regression was used to assess the association between serum vitamin D levels and BV. Additionally, smoothing curve fitting and subgroup analyses were performed to explore potential non-linear relationships and effect modifications.ResultsA total of 1,397 adult women were included. After adjusting for multiple covariates, serum vitamin D levels showed a significant non-linear negative association with BV risk. Subgroup analyses revealed that this association was not statistically significant among certain ethnic groups and women with lower body mass index (BMI).ConclusionSerum vitamin D levels were non-linearly and negatively associated with the risk of bacterial vaginosis in adult women in the United States. Notably, the association was no longer present at serum vitamin D concentrations ≥63.1 nmol/L, which may inform future research.